2015
DOI: 10.4049/jimmunol.1402183
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase PTPN4 Preferentially Inhibits TRIF-Dependent TLR4 Pathway by Dephosphorylating TRAM

Abstract: TLR4 recruits TRIF-related adaptor molecule (TRAM, also known as TICAM2) as a sorting adaptor to facilitate the interaction between TLR4 and TRIF and then initiate TRIF-dependent IRF3 activation. However, the mechanisms by which TRAM links downstream molecules are not fully elucidated. In this study, we show that TRAM undergoes tyrosine phosphorylation upon TLR4 activation and that is required for TLR4-induced IRF3 activation. Protein tyrosine phosphatase nonreceptor type 4 (PTPN4), a protein tyrosine phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 33 publications
0
33
1
Order By: Relevance
“…Three days later, peritoneal exudate cells were harvested and incubated. Two hours later, nonadherent cells were removed and the adherent monolayer cells were used as peritoneal macrophages (19)(20)(21). THP-1, HeLa, and human embryonic kidney (HEK) 293T cells were obtained from American Type Culture Collection (Manassas, VA).…”
Section: Mice and Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Three days later, peritoneal exudate cells were harvested and incubated. Two hours later, nonadherent cells were removed and the adherent monolayer cells were used as peritoneal macrophages (19)(20)(21). THP-1, HeLa, and human embryonic kidney (HEK) 293T cells were obtained from American Type Culture Collection (Manassas, VA).…”
Section: Mice and Cell Culturementioning
confidence: 99%
“…Luciferase activities were measured with a Dual-Luciferase reporter assay system (Promega) according to the manufacturer's instructions (19)(20)(21). Data are normalized for transfection efficiency by subtracting firefly luciferase activity with that of Renilla luciferase.…”
Section: Luciferase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we showed that rabies virus (RABV) peptides encoding a PBM can target the PDZ domain of PTPN4 (PTPN4-PDZ) and antagonize the function of PTPN4, leading to cell death (6). We optimized such pro-apoptotic peptides and designed the Cyto8-RETEV sequence, that is so far the most affine ligand of PTPN4-PDZ and the best inducer of cell death (15).Four endogenous partners of PTPN4 have been reported: the glutamate receptor ␦2 and ⑀ subunits, the T-cell receptor subunit, the CrkI oncoprotein, and the TRIF (TIR domain-containing adaptor-inducing interferon-B)-related adaptor molecule TRAM (3,5,16,17). Nevertheless, the natural ligands of PTPN4 involved in the regulation of cell homeostasis remain unknown.…”
mentioning
confidence: 99%